Pendekatan Kebudayaan dalam Membangun Ketahanan dan Keamanan Insani: Sebuah Kajian Strategis - Sugeng, Sugeng; Fitriana, Diana; Aidy, Widya (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2024)
This article examines the concept of culture as a sustainable strategy according to Cornelis Anthonie van Peursen, a philosopher who views culture as a fundamental instrument for human survival and adaptation. Van Peursen outlines the development of culture through three main stages: myth, ontology, and function, each reflecting the evolution of how humans understand and manage reality. In the context of rapid globalization and technological change, this article highlights the relevance of Van Peursen's approach in addressing contemporary challenges, such as identity crises and environmental changes. This analysis also identifies the strengths and limitations of Van Peursen's perspective and offers reflections on the role of culture as a dynamic strategy that can help modern society achieve social and ecological sustainability. Thus, this article contributes to a deeper understanding of culture as an essential adaptive mechanism for human survival.